MOTIVASI, KOMITMEN ORGANISASIONAL DAN KEPUASAN KERJA KARYAWAN DI WAROENG SPESIAL SAMBAL, JATINANGOR - Kalifatullah Ermaya, Sir; Mujdalipah, Siti (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2019)
The food service industry has received many challenges in the current era of disruption of the industrial revolution 4.0. Given the urgency of increasing the Motivation and Organizational Commitment in one of the restaurants in Jatinangor, the title of this study is